2015
DOI: 10.1289/ehp.1409525
|View full text |Cite
|
Sign up to set email alerts
|

Interweaving Knowledge Resources to Address Complex Environmental Health Challenges

Abstract: BackgroundComplex problems do not respect academic disciplinary boundaries. Environmental health research is complex and often moves beyond these boundaries, integrating diverse knowledge resources to solve such challenges. Here we describe an evolving paradigm for interweaving approaches that integrates widely diverse resources outside of traditional academic environments in full partnerships of mutual respect and understanding. We demonstrate that scientists, social scientists, and engineers can work with go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…The SRP's unique transdisciplinary approach has created new perspectives, empowering researchers to understand some of the toughest environmental health problems, and has led to diverse accomplishments for a single grant funding program (e.g., Ref. [14][15][16]). SRP-funded research has led to the development of remediation and site monitoring tools involved in the cleanup of potentially hazardous substances.…”
Section: Maximizing the Impact Of Srp Researchmentioning
confidence: 99%
“…The SRP's unique transdisciplinary approach has created new perspectives, empowering researchers to understand some of the toughest environmental health problems, and has led to diverse accomplishments for a single grant funding program (e.g., Ref. [14][15][16]). SRP-funded research has led to the development of remediation and site monitoring tools involved in the cleanup of potentially hazardous substances.…”
Section: Maximizing the Impact Of Srp Researchmentioning
confidence: 99%
“…Broadly, this form of transparency is not about data in the abstract but instead incorporates how participatory knowledge making includes not only the standard scientific and industry perspectives that have historically shaped environmental regulations, but also the diverse, situated perspectives of multiple marginalized communities. Public and environmental health research has shown that in many cases, the incorporation of participant-centred, local knowledge and values has improved scientific design and rigor (Anderson et al, 2015).…”
Section: Edgi As a Place Struggling With Edj In Practicementioning
confidence: 99%
“…Most relevant to this analysis, Balazs and Ray [ 1 ] developed a drinking water disparities framework which includes the natural, built and sociopolitical environments, interacting at regional, community and household levels, to “explain environmental injustice in the context of [municipal] drinking water” in the San Joaquin Valley in California. Addressing complex environmental health problems is challenging and requires “interweaving multiple knowledge resources,” including community expertise [ 88 ]. The use of community based participatory research (CBPR) by tribes/minority communities and their academic partners to bring such a comprehensive approach to addressing public environmental health issues is well documented [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Introductionmentioning
confidence: 99%
“…Addressing complex environmental health problems is challenging and requires “interweaving multiple knowledge resources,” including community expertise [ 88 ]. The use of community based participatory research (CBPR) by tribes/minority communities and their academic partners to bring such a comprehensive approach to addressing public environmental health issues is well documented [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. This approach provides a mechanism to begin to create more integrated datasets, including community expertise.…”
Section: Introductionmentioning
confidence: 99%